A Review: Reliability Assessment of Isolated Phase Busduct Through FMEA and RCFA Methodologies - Iskandar, Handoko Rusiana; Ahmad Daelami; Awang Rahmawan Prakoso; Cepi Arifin; Miftah Farid (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2025)
This research discuss the reliability of the Isolated Phase Busduct (IPB) geothermal generating unit still needs to be improved because the same disturbances still occur, where in the 2018-2023 period these disturbances have contributed to a Loss Production Opportunity of around 65 billion rupiah. Therefore, this research will provide suggestions or suggestions for what factors need to be improved so that the reliability of IPB in each geothermal power plant unit increases. The methods used in this research are failure mode and effect analysis (FMEA) and the Root Cause Failure Analysis (RCFA) method, where FMEA helps in identifying potential failures and determining mitigation priorities and determining the value of the Risk Priority Number (RPN), Root Cause Failure Analysis (RCFA) reveals the main causes of failures that have occurred, from these two methods it is known that the disturbances that occur can actually be identified earlier by 91.2% as well as factors such as manufacture design, aging equipment, improper installation, Lack of Quality Control, and inappropriate mobilization must be eliminated in an effort to increase IPB's reliability where these factors must be considered from the project phase to the operational phase.